2008
DOI: 10.4067/s0718-58392008000200009
|View full text |Cite
|
Sign up to set email alerts
|

House Fly (Musca domestica L.) (Diptera Muscidae) Development in Different Types of Manure

Abstract: Animal production units with different management systems can be found along the Huasco Valley, Region of Atacama, Chile. These constitute sources of house flies (Musca domestica L.) and other vector fly species that cause damage to animals and nuisance problems in urban areas. In order to asses the importance of fly breeding sources, an experiment was carried out under laboratory conditions to evaluate different types of animal manure and composted swine manure. Time of larval development, larva mortality, pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 7 publications
1
24
0
3
Order By: Relevance
“…The supplemental use of maggots in animal feed may improve animals' immune systems and reduce antibiotic usage Dong et al, 2013). Excitingly, there have been reports on the culture of housefly-maggot in feces (Amano, 1985;Golubeva, 1986;Iniguez-covarrubias et al, 1994;Larrain and Salas, 2008). Moreover, manure of poultry and pig that has been treated with maggots becomes somewhat granular, which is suitable for further composting without bulking agents (Miller et al, 1974;Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…The supplemental use of maggots in animal feed may improve animals' immune systems and reduce antibiotic usage Dong et al, 2013). Excitingly, there have been reports on the culture of housefly-maggot in feces (Amano, 1985;Golubeva, 1986;Iniguez-covarrubias et al, 1994;Larrain and Salas, 2008). Moreover, manure of poultry and pig that has been treated with maggots becomes somewhat granular, which is suitable for further composting without bulking agents (Miller et al, 1974;Zhu et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…The principle involvement of housefl ies in the life cycle of H. muscae is known more than 100 years ago but detailed examinations how the parasite infl uence the larval development of housefl ies are rare. Horse faeces were reported to be a good breeding substrate for housefl ies in most of the early observations on the life cycle of this insect (Howard, 1898;Leikina, 1943) while other sources showed a poor development of fl y larvae in horse manure (Larrain & Salas, 2008;Machtinger, 2011). Hewitt (1910 concluded that larvae of M. domestica can develop in all kind of decaying animal or vegetable matter when fermentation is occurring and the development time depends on quality of the food, temperature and moisture.…”
Section: Discussionmentioning
confidence: 99%
“…html), although it is better known for its ubiquitous activity of feeding and developing on decaying organic matter. Common substrates are associated with human, horse, bovine, swine, bird, sheep, and goat feces, decomposing plant material, kitchen waste, cut grass, and carrion (Larraín and Salas 2008). Musca domestica is a species of medical and agricultural importance due to its ability to transmit about 100 human and animal diseases via its mouthparts, vomit, feces, and body surface (Förster et al 2007;Morey and Khandagle 2012).…”
Section: Methodsmentioning
confidence: 99%